Mukena: A balance between the Indonesian women's prayer dress and the hadiths on the prayer of prophet's wives | موكينا: موازنة بين لباس صلاة المرأة الإندونيسية وأحاديث صفة صلاة أمهات المؤمنين - Fatihunnada Fatihunnada; Nur Faricha; Hasan Basri Salim (Al-Zahra : Journal for Islamic and Arabic Studies, 2021)
Mukena is a women's prayer dress in Indonesia. It is well known that the Nine Saints knew her in the fourteenth century AD, but the truth is that Nyai Mukena first knew her in Cirebon. Mokina is considered an Indonesian women's prayer dress. The prayer dress has standards that must be met for the validity of its use in prayer. The mothers of the believers wore the dress of prayer for the Arabs in the past, as mentioned in some narrations. This research analyzes Mukena's hadiths about the dress of the mothers of the believers' prayer.This research is written using the analytical method by searching for hadiths of the prayer dress of the mothers of the believers, looking at the explanation of the hadiths, and analyzing them in the Arabic traditions in Mukena. The method of writing this research is the library method of collecting sources, references and scientific theses related to this research.One of the results of this research is that Mukena is the prayer dress of Indonesian Muslim women. It is the result of Indonesian culture, and is said to be the result of adaptation by the Nine Saints in the revival of Islamic law. The hadiths describing women’s prayer dress indicate that Islamic law has standards in prayer dress, which are not to show a woman’s private parts. Islamic law does not require the form of dress, and all Muslim women must use the local dress that meets the conditions for covering the private parts of the body in prayer.